PENERAPAN FILSAFAT TRI HITA KARANA DALAM PEMANFAATAN LIMBAH ORGANIK UNTUK AKUAKULTUR BERKELANJUTAN DI DESA TUWED - I Gede Pasek Mancapara; Ida Ayu Ngurah Deepika Ishana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The community of Tuwed Village in Jembrana Regency is predominantly engaged in freshwater fish farming. High feed costs remain a major challenge for fish farmers. To address this, the community, in collaboration with the village government, developed charoen, an alternative feed made from organic waste of infertile eggs. This initiative reflects the Tri Hita Karana philosophy, which emphasizes harmony among humans, the environment, and the divine through religious practices, local fermentation technology, and traditional social structures. This study adopts a qualitative case study approach, grounded in community participation theory and cultural ecology, to examine the integration of local wisdom into sustainable aquaculture. The findings reveal a systemic synergy between the government, community, and the Tri Hita Karana philosophy, resulting in an efficient and culturally rooted aquaculture model. This model not only improves economic welfare but also supports environmental preservation and the continuity of cultural values, with potential for application in other regions.